2014
DOI: 10.1155/2014/419653
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Control Trial of the Impact of a Computer-Based Activity Programme upon the Fitness of Children with Autism

Abstract: The poor levels of fitness in children with autism are prompting concern for the children's future health. This study looked to assess if a computer-based activity programme could improve fitness levels (as reflected in cardiopulmonary function) of these children, and achieve a reduction in their body mass index. In a randomised controlled trial, 50 children with autism (of which 33 were under the age of 11 years and 39 were boys) were allocated to an intervention group which encouraged them to use the Nintend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 54 publications
3
40
0
10
Order By: Relevance
“…This category of outcomes was shown to be greatly affected for experimental groups by the implementation of physical activity interventions ( g ≥ 0.80). Intervention modalities utilized included a computer‐based activity program (Dickinson & Place, ), exergaming (Hilton et al, ), trampolining (Laurenco et al, ; Giagazoglou 2013), physical training (Pan, ), and a Simulated Developmental Horse‐Riding Program (SDHRP) (Wuang et al, ). Deficits in skill‐related fitness—for example, related to postural stability (Molloy, Dietrick, & Bhattacharya, ), body coordination, and agility (Pan, 2012)—are prevalent among youth with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This category of outcomes was shown to be greatly affected for experimental groups by the implementation of physical activity interventions ( g ≥ 0.80). Intervention modalities utilized included a computer‐based activity program (Dickinson & Place, ), exergaming (Hilton et al, ), trampolining (Laurenco et al, ; Giagazoglou 2013), physical training (Pan, ), and a Simulated Developmental Horse‐Riding Program (SDHRP) (Wuang et al, ). Deficits in skill‐related fitness—for example, related to postural stability (Molloy, Dietrick, & Bhattacharya, ), body coordination, and agility (Pan, 2012)—are prevalent among youth with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…It was significant, therefore, that within the outcome of muscular strength and endurance, experimental groups outperformed control groups to a large effect ( g = 0.818). Studies measuring these outcomes utilized a number of intervention modalities, such as Nintendo Wii exergaming (Dickinson & Place, ), aquatic exercise programs (Fragala‐Pinkham, Haley, & O'Neil, ; Fragala‐Pinkham, Haley, & O'Neil, ; Pan, ), and horse riding programs (Wuang et al, ). The research in this area highlights some challenges, and areas in need for future study; for example, Fragala‐Pinkham et al () discuss that the 14‐week program may not have been of sufficient duration to show changes; perhaps the longer duration of other interventions that showed to positively affect muscular strength and/or endurance contribute to their success (e.g., 20‐week intervention: Wuang et al, ; one‐year intervention: Dickinson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Children with autism have greater difficulties than typically developed children with participating in physical activity because of the nature of their motor and environmental difficulties. Some studies have found that children with autism are less active than children without disabilities [ 35 ]. It is possible to reduce the PA practice because of an existing motor impairment that causes less opportunities to develop and enrich existing and new physical abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Dickinson and Place (2014) sought to utilize the engagement that many children with multiple impairments, specifically ID and autism, have in electronics to improve physical health. In a randomized controlled study, they assigned children with multiple impairments to a Nintendo Wii exercise game, with hopes that the children's markers of physical fitness would improve significantly over the course of a year compared to a control group.…”
Section: Physical Activity Interventionsmentioning
confidence: 99%